Hypoxia-inducible factor-1α inhibition augments efficacy of programmed cell death 1 antibody in murine prostatic cancer models. Issue 6 (23rd March 2022) - Shen, Zhonghua; Pei, Qiong; Zhang, Huimin; Yang, Chao; Cui, Haijun; Li, Bin; Liu, Jian; Bo, Zhiqiang; Wei, Feng; Zhang, Min; Liu, Chuang
Abstract : This study was designed to explore whether hypoxia-inducible factor-1α (HIF-1α) inhibitor could enhance immunotherapy efficacy in prostate cancer. Western blot was used to detect the expression of HIF-1α in the tumor and peritumor tissues from prostate cancer patients. The analysis from Cancer Genome Atlas database was used to show an association between HIF-1α expression and survival rate in prostate cancer patients. Murine prostate cell–derived xenograft (CDX) model was set up in both nude mice and BALB/c mice to observe the therapeutic effect of HIF-1α inhibitor IDF-11774. Protein expression of HIF-1α, as well as changes in the immune microenvironment, was detected. Moreover, the synergistic antitumor effect of IDF-11774 and PD-1 antibody was detected in another murine prostate cancer model. HIF-1α was found to have higher expression in prostate cancer tumor tissue than in peritumor tissue, and the expression level was negatively correlated with survival rate ( P = 0.0157). HIF-1α inhibitor IDF-11774 reduced tumor volume and exhibited better efficacy in BALB/c mouse model ( P < 0.0001) with normal immune system, with the same suppression level against HIF-1α. HIF-1α inhibitor reduced CD45 + CD11b + Gr-1 + myeloid-derived suppressor cells ( P = 0.0027) and CD45 + CD11b + F4/80 + CD206 hi M2 macrophages ( P = 0.0059) but increased the abundance of CD45 + CD3 + CD8 + T cells ( P = 0.0002) and CD45 + CD3 + CD4 + T cells ( P = 0.0001) in tumor-infiltrating immune cells. The same synergistic effect was observed in RM-1 murine prostate CDX tumor model. HIF-1α inhibition augmented the antitumor efficacy of immune checkpoint inhibitor PD-1 antibody in murine prostate cancer models, probably through modulating the immunosuppressive microenvironment.